A Core Set of Outcome Measures for Adults With Neurologic Conditions Undergoing Rehabilitation: A CLINICAL PRACTICE GUIDELINE. Issue 3 (July 2018) - Moore, Jennifer L.; Potter, Kirsten; Blankshain, Kathleen; Kaplan, Sandra L.; O'Dwyer, Linda C.; Sullivan, Jane E.
Abstract : Background: Use of outcome measures (OMs) in adult neurologic physical therapy is essential for monitoring changes in a patient's status over time, quantifying observations and patient-reported function, enhancing communication, and increasing the efficiency of patient care. OMs also provide a mechanism to compare patient and organizational outcomes, examine intervention effectiveness, and generate new knowledge. This clinical practice guideline (CPG) examined the literature related to OMs of balance, gait, transfers, and patient-stated goals to identify a core set of OMs for use across adults with neurologic conditions and practice settings. Methods: To determine the scope of this CPG, surveys were conducted to assess the needs and priorities of consumers and physical therapists. OMs were identified through recommendations of the Academy of Neurologic Physical Therapy's Evidence Database to Guide Effectiveness task forces. A systematic review of the literature on the OMs was conducted and additional OMs were identified; the literature search was repeated on these measures. Articles meeting the inclusion criteria were critically appraised by 2 reviewers using a modified version of the COnsensus-based Standards for the selection of health Measurement INstruments. (COSMIN) checklist. Methodological quality and the strength of statistical results were determined. To be recommended for the core set, the OMs needed to demonstrate excellent psychometric properties in high-quality studies across neurologic conditions. Results/Discussion: Based on survey results, the CPG focuses on OMs that have acceptable clinical utility and can be used to assess change over time in a patient's balance, gait, transfers, and patient-stated goals. Strong, level I evidence supports the use of the Berg Balance Scale to assess changes in static and dynamic sitting and standing balance and the Activities-specific Balance Confidence Scale to assess changes in balance confidence. Strong to moderate evidence supports the use of the Functional Gait Assessment to assess changes in dynamic balance while walking, the 10 meter Walk Test to assess changes in gait speed, and the 6-Minute Walk Test to assess changes in walking distance. Best practice evidence supports the use of the 5 Times Sit-to-Stand to assess sit to standing transfers. Evidence was insufficient to support use of a specific OM to assess patient-stated goals across adult neurologic conditions. Physical therapists should discuss the OM results with patients and collaboratively decide how the results should inform the plan of care. Disclaimer: The recommendations included in this CPG are intended as a guide for clinicians, patients, educators, and researchers to improve rehabilitation care and its impact on adults with neurologic conditions. The contents of this CPG were developed with support from the APTA and the Academy of Neurologic Physical Therapy (ANPT). The Guideline Development Group (GDG) used a rigorous review process and was able to freely express its findings and recommendations without influence from the APTA or the ANPT. The authors declare no competing interest. Video Abstract available for more insights from the authors (see Video, Supplemental Digital Content 1, available at:http://links.lww.com/JNPT/A214 . Abstract : Supplemental Digital Content is Available in the Text.